How Macroeconomic Indicators Drive Food Production in OIC Countries? - Luthfi, Faishol; Ardelia, Aya Sofia; Arminingsih, Diah (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: This research prioritizes a more in-depth analysis of OIC member countries with different income categories. The research also focuses on developing a more robust and integrated modeling framework that can capture the dynamic interactions between inflation, economic growth, and food production. Research Objectives: This study investigates the impact of economic growth and inflation on food production in both the short and long term. Research Methods: This study uses panel data from 40 OIC member countries from 1992 to 2021. This study employs Panel Autoregressive Distributed Lag (PARDL) and categorizes OIC member countries based on income classifications: High-Income, upper-middle, lower-middle, and Low-Income countries. Empirical Results: The findings indicate that economic growth and inflation substantially impact food production over the long term. Certain countries exhibit a beneficial impact, whereas others demonstrate a detrimental effect. Implications: This research can provide new insights into the complex relationship between macroeconomic indicators and food availability, and it can be used to inform policymaking recommendations. In addition, the findings can support policymakers in formulating more effective strategies to shift policy towards sustainability. JEL Classification: C31, E23, O13 How to Cite:Luthfi, F., Ardelia, A. S., & Arminingsih, D. (2025). How Macroeconomic Indicators Drive Food Production in OIC Countries: A Panel ARDL Analysis. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 325-338. https://doi.org/10.15408/sjie.v14i2.45673.